Dioxin Disrupts Dynamic DNA Methylation Patterns in Genes That Govern Cardiomyocyte Maturation. (5th October 2020) - de Gannes, Matthew; Ko, Chia-I; Zhang, Xiang; Biesiada, Jacek; Niu, Liang; Koch, Sheryl E; Medvedovic, Mario; Rubinstein, Jack; Puga, Alvaro
Abstract: Congenital heart disease (CHD), the leading birth defect worldwide, has a largely unknown etiology, likely to result from complex interactions between genetic and environmental factors during heart development, at a time when the heart adapts to diverse physiological and pathophysiological conditions. Crucial among these is the regulation of cardiomyocyte development and postnatal maturation, governed by dynamic changes in DNA methylation. Previous work from our laboratory has shown that exposure to the environmental toxicant tetrachlorodibenzo- p -dioxin (TCDD) disrupts several molecular networks responsible for heart development and function. To test the hypothesis that the disruption caused by TCDD in the heart results from changes in DNA methylation and gene expression patterns of cardiomyocytes, we established a stable mouse embryonic stem cell line expressing a puromycin resistance selectable marker under control of the cardiomyocyte-specific Nkx2-5 promoter. Differentiation of these cells in the presence of puromycin induces the expression of a large suite of cardiomyocyte-specific markers. To assess the consequences of TCDD treatment on gene expression and DNA methylation in these cardiomyocytes, we subjected them to transcriptome and methylome analyses in the presence of TCDD. Unlike control cardiomyocytes maintained in vehicle, the TCDD-treated cardiomyocytes showed extensive gene expression changes, with a significant correlation between differential RNA expression and DNA methylation in 111 genes, many of which are key elements of pathways that regulate cardiovascular development and function. Our findings provide an important clue toward the elucidation of the complex interactions between genetic and epigenetic mechanisms after developmental TCDD exposure that may contribute to CHD.